Prevalence, associated risk factors and antimicrobial susceptibility pattern of thermophilic Campylobacter spp. of ovine carcass at Addis Ababa Abattoir Enterprise, Ethiopia - Hailemariam, S. (Addis Ababa University, 2014)
The food borne-thermophilic Campylobacter species are considered to be the leading cause of human gastroenteritis worldwide with emerging antimicrobial resistant strains. Consumption of raw or under cooked meat being an important source for zoonotic infection; poultry play the major role followed by other food animals especially sheep which is a widely consumed protein source for the pubic, Ethiopia. A cross sectional abattoir based study was conducted on sheep and the carcass destined for slaughter at Addis Ababa Abattoir Enterprise. To determine the prevalence of thermophilic Campylobacter spp. 160 carcass and 160 rectal swabs were bacteriologically examined where 21(13.1%) and 12(7.5%) thermophilic Campylobacter spp. were isolated respectively. Biochemical test results of the carcass isolates indicated 12 (57.1%) to be C. jejuni, 6(28.6%) C. coli and 3(14.3%) C. lari. Similar examination of abattoir environment pool samples of 8 sampling days revealed 7(87.5%) to be positive for the thermophilic Campylobacters. None of wash water samples were positive for the bacteria. Antimicrobial susceptibility pattern test towards twelve antimicrobials using standard disk diffusion method resulted higher resistance percentage (42.1%) for amixacillin-clavulanic acid and (42.1%) kanamycin followed by sterptomycine, oxytetracyline and compound sulphonamide (33.3%) each. In the present study, most isolates were susceptible to ceftriaxone and clindamycin with (4.8%) resistance percentage each, and a lesser degree to erythromycin (9.5%). Multi drug resistance is observed in 52.4% of the isolates examined. Concluding, raw mutton is a potential source of campylobacteriosis with varied antimicrobial resistant strains for the public hence hygienic meat production in abattoirs and wise use of veterinary drugs are inevitable to render the public health.